2024
DOI: 10.17507/tpls.1401.11
|View full text |Cite
|
Sign up to set email alerts
|

Victimization in Walker’s The Color Purple: A Critical Stylistic Analysis

Azhar Hassan Sallomi,
Iman Mingher Obied

Abstract: The current paper investigates woman’s victimization in Alice Walker’s novel The Color Purple from a critical stylistic perspective. It aims to show how victimization is realized linguistically in terms of some toolkits mentioned in Jeffries’s (2010) framework. Additionally, it aims to reveal the ideological implication of these toolkits in the data under study. The study adopts a mixed method of qualitative and quantitative approaches in the analysis. The researchers find out that woman’s victimization is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Their study examines the exploitation of linguistic resources in the construction of certain ideologies. Similarly, Sallomi and Obied (2024) have carried out a critical stylistic analysis of The Color Purple (1982) by Alice Walker in their research study. They found that "women's victimization is recognized in The Color Purple through various syntactic triggers that symbolize Jeffries' conceptual tools" (Sallomi & Obied, 2024, p. 98).…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study examines the exploitation of linguistic resources in the construction of certain ideologies. Similarly, Sallomi and Obied (2024) have carried out a critical stylistic analysis of The Color Purple (1982) by Alice Walker in their research study. They found that "women's victimization is recognized in The Color Purple through various syntactic triggers that symbolize Jeffries' conceptual tools" (Sallomi & Obied, 2024, p. 98).…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…They found that "women's victimization is recognized in The Color Purple through various syntactic triggers that symbolize Jeffries' conceptual tools" (Sallomi & Obied, 2024, p. 98). Their study concludes that among the conceptual tools provided by Jeffries, the tool of 'representing actions/states/events' is the most common among others as it is interconnected with the violent acts that lead to victimization of women in the novel (Sallomi & Obied, 2024).…”
Section: Methodological Frameworkmentioning
confidence: 99%